Crypto-Geological Fiqh Law: Analysis of Maqashid Syariah on the Use of Blockchain and Smart Contract in the Distribution of Cross-Country Natural Disaster Compensation Funds - Azhari Azhari (Rechtsvinding, 2026)
Increasing frequency disaster natural cross- country demands system fast, transparent and accountable distribution of compensation funds, but system conventional Still face constraint bureaucracy layered, chain intermediation long, and fragmentation regulations between countries that hinder effectiveness help humanity. Blockchain technology and smart contracts are here as solution potential, but its use in Islamic philanthropy requires justification from perspective maqashid sharia so as not to cause harm new. Research This is studies literature that analyzes use of blockchain and smart contracts in distribution of compensation funds disaster natural across countries through framework Maqashid Syariah. Research results disclose that blockchain architecture provides benefit significant in the form of transparency and accountability that contribute to protection property, as well as efficiency supporting distribution protection soul, even though keep potential understanding such as pseudo- anonymous, consumption energy excessive, and disparity digital infrastructure. Smart contract scheme aligned with principle clarity contract and prevent gharar, however its rigidity contradictory with principle emergency and have vulnerability in the oracle problem. Dimension cross- country causes tension between sovereignty laws and regulations give help humanity, which requires framework law transnational adaptive. Synthesis study produce framework Islamic ethics for blockchain governance based on trust, maslahah, shura, hisbah, and balance transparency-privacy. Implementation results study realized in prototype consortium blockchain system with governance participatory, emergency override mechanism, decentralized oracle, privacy differential, as well as an independent sharia supervisory board.